If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying cos(x) + -1cos(7x) = sen(4x) Multiply cos * x cosx + -1cos(7x) = sen(4x) Remove parenthesis around (7x) cosx + -1cos * 7x = sen(4x) Reorder the terms for easier multiplication: cosx + -1 * 7cos * x = sen(4x) Multiply -1 * 7 cosx + -7cos * x = sen(4x) Multiply cos * x cosx + -7cosx = sen(4x) Combine like terms: cosx + -7cosx = -6cosx -6cosx = sen(4x) Remove parenthesis around (4x) -6cosx = ens * 4x Reorder the terms for easier multiplication: -6cosx = 4ens * x Multiply ens * x -6cosx = 4ensx Solving -6cosx = 4ensx Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Divide each side by '-6osx'. c = -0.6666666667eno-1 Simplifying c = -0.6666666667eno-1
| 6(2x-3)-13=2(x-1) | | 3=2b+5b | | 5(3y-11)=-10 | | 3y+27=6x | | x+(x+0.39)+(x+0.41)=10.25 | | -4y=12y-64 | | 4+-2g=16 | | 19-5x-8+7x= | | -7-14=35 | | 16-16x-x^2=4x+5 | | 52=3w+13 | | 3=-3(x+10) | | 5x+4x-45=60-6x | | 5y+y=48 | | 1x-.30x=525 | | 16t-t-5s-9t= | | -18.99=x+6.23 | | 9w-w=48 | | 4x+3x=15 | | 15i-4f-17i+3f= | | x-19.8=-4.24 | | 6cos(x)+8sin(x)=0 | | 3(2x-3)-13=2(x-1) | | 2n-16=14 | | 9u-v-11u+v= | | xt(-100)=-99 | | 6.2+1.2=8.9x | | ax+bx-3=-8 | | d-14.2=-18.7 | | 10y-5z-y-3z= | | (3x-2)(5x+1)(x)= | | k-4/=3 |